Optimal capital income taxation, investment subsidies and redistribution in a neoclassical growth model - Günther Rehme (Technische Universität Darmstadt, Department of Law and Economics, 2007)
In this paper I readdress the result that capital income taxes are bad instruments for pure redistribution and should be zero in the long run. In a neoclassical growth model a capital income cum investment subsidy tax, which is not distorting accumulation, is considered to investigate if net capital income taxes used for pure redistribution are zero in a long-run optimum. I find that capital income taxes may be nonzero, depending on the political power of those who receive redistributive transfers, the distribution of pre-tax factor incomes, and the intertemporal elasticity of substitution.
Keywords: O41; H21; D33; 330; Growth; Redistribution; Investment Subsidies; Capital Income Taxes; Kapitalertragsteuer; Optimale Besteuerung; Steuerinzidenz; Wachstumspoltheorie; Neoklassik